A non-dispersion strategy for large-scale production of ultra-high concentration graphene slurries in water - Lei Dong (Nature Portfolio, 2018)
Large-scale graphene production remains challenging because of the tendency of graphene to stack with itself, which requires its dispersion in large amounts of solvent. Here the authors achieve the environmentally favourable production of highly concentrated graphene in water through a non-dispersion, flocculation strategy.